The Effect of Casein Phosphopeptide-Amorphous Calcium Phosphate on Molar-Incisor Hypomineralisation: A Pilot Study - KARGÜL, BETÜL (QUINTESSENCE PUBLISHING CO INC, 2017)
Purpose: To evaluate the effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and casein phosphopeptide-amorphous calcium fluoride phosphate (CPP-ACFP) application on noncarious MIH (molar-incisor hypomineralisation) lesions using a DIAGNOdent device (KaVo), which measures laser fluorescence within the mineral structure of the tooth. Materials and Methods: A total of 461 subjects age 7-12 (mean +/- SD was 9.9 +/- 1.6) years were examined. Fifty-four children were diagnosed with MIH and divided into 2 groups. A total of 38 teeth met the inclusion criteria and were included in the study. Group 1 subjects (n = 15) used a paste containing 10% CPP-ACP, and group 2 subjects (n = 23) used a paste containing 10% CPP-ACP with 0.2% NaF (CPP-ACFP) for one month. Results: After the application of the pastes for one month, significant decreases were found in the mean DIAGNOdent readings for both groups (CPP-ACP p = 0.0015 and CPP-ACFP p = 0.0001). However, the percentage decreases in both groups were not significantly different from each other (60.4% and 45.5% in CPP-ACP and CPP-ACFP groups, respectively). Conclusion: This pilot study shows that using CPP-ACP and CPP-ACFP had a positive effect in reducing hypomineralisation on enamel surfaces of MIH-diagnosed teeth for a one month period. It is important to diagnose molar-incisor hypomineralisation at an early stage to prevent excessive caries develeopment. Therefore, further clinical studies are necessary on the long-term application of these kinds of nanocomplexes.
Keywords: CPP-ACP; CPP-ACFP; DIAGNOdent; fluoride; molar-incisor hypomineralisation; OCCLUSAL CARIES DETECTION; LASER FLUORESCENCE; CPP-ACP; ENAMEL HYPOMINERALISATION; FLUORIDE RELEASE; PERMANENT MOLARS; IN-VIVO; LESIONS; REMINERALIZATION; DIAGNODENT